Estabilidade da propriedade institucional de ações e sua relação com práticas de gerenciamento de resultados - Santos, Lorena Ingrid de Lima e (2020)
This study arises from the need to understand more about how institutional investors operate in Brazilian companies, and, if their presence and volatility exert some type of reduction in the adherence of earnings management practices by their investees. In addition, it is questioned whether this result is attributable to any type of institutional investor. For this analysis, the volatility of institutional investors' holdings in unregulated and non-financial companies listed on the Brazilian stock exchange (B3) was verified, during the period from 2010 to 2018, which contained some institutional investors in their shareholding structure, constituting a sample of 159 companies. Thus, the metrics STDI and PROP, proposed by Elyasiani, Jia and Mao (2010), were used. These are calculated in their total values, for the entire group of institutional and individual investors, considering its four main types: Banks, Insurance Companies, Investment Funds and Holdings. As proxies for earnings management, the two main types were measured: through discretionary accruals (AEM), in which the Pae model (2005) was adopted, and through operational activities (REM), which were measured by the models of Roychowdhury (2006). The results indicated that companies with stable shareholders of the Banks-type are less associated with AEM practices, demonstrating an active monitor profile, differently from what is estimated in the literature. It was also evident that companies with stable Holdings-type shareholders have less adherence to REM-type strategies, attributing it to institutional activism. And in bigger participation proportions of the Insurance-company-type shareholder, a greater association with the management of AEM and REM results was evidenced, granting this type of investor a passive ownership profile. The relevance of these findings is to understand more and more about the actions of these investors, how important it is to consider their heterogeneity of their objectives, the search for short or long term gains, and the efficiency of their monitoring in mitigating earnings management practices.